2006
DOI: 10.1021/je0600092
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Thermal Diffusivities, Thermal Conductivities, and Sound Speeds of Room-Temperature Ionic Liquids by the Transient Grating Technique

Abstract: We report measurements of thermal diffusivity of several room-temperature ionic liquids (RTILs) using the transient grating method. Measurements are carried out using ionic liquids with small concentrations of an inert dye that is excited by the 532 nm output of a Nd:YAG laser in a grating with a fringe spacings of (92 and 104) μm. The experiments give thermal diffusivities from which thermal conductivities can be determined, sound speeds, and acoustic damping parameters for seven ionic liquids. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
134
4
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(164 citation statements)
references
References 29 publications
22
134
4
4
Order By: Relevance
“…However, contrary to many 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 , only one isothermal value is available to date. 10 Generally, it appears that the agreement between the values determined in this study and the values reported in the literature is acceptable ( Figure 6). With the exception of the isothermal data of Demizu et al 17 and Fukuda et al 18 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 16 method show very...…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 77%
See 2 more Smart Citations
“…However, contrary to many 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 , only one isothermal value is available to date. 10 Generally, it appears that the agreement between the values determined in this study and the values reported in the literature is acceptable ( Figure 6). With the exception of the isothermal data of Demizu et al 17 and Fukuda et al 18 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 16 method show very...…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 77%
“…Using a transient grating (TG) method, 14 additional experimental results have been reported by Frez et al 10 (for seven RTILs) and Kozlov et al 11 (for four RTILs). Unfortunately, in both cases measurements have been carried out only at single frequency at 296.85 K or 301 K, respectively.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, there is scant literature that can be found for thermal conductivity measurement of ILs. Frez et al utilized the transient grating method for the thermal conductivity measurement of 7 ILs [35]. In the work of Ge et al, the transient hot-wire method was utilized to measure the thermal conductivity of 11 pure ILs [36].…”
Section: Introductionmentioning
confidence: 99%
“…Frez et al [35] are the only researchers who experimentally measured the thermal diffusivity of pure ILs according to our own knowledge. In the 3 work of Frez et al, transient grating technique was utilized for measurement of pure ILs thermal diffusivity [35]. We found the thermal diffusivity data of ILs are rarely known in the current literatures.…”
Section: Introductionmentioning
confidence: 99%